Conceptualizing ‘Science’ in the Photography Collections at the National Science and Media Museum - Belknap, Geoffrey (Scientia Canadensis, 2022)
Focusing on the internationally significant photographic collections at the National Science and Media Museum (Bradford, UK), this article explores the central questions: What counts as ‘scientific’ in a museum dedicated to the history of photography (as well as film, television, and digital media)? And what is the place of photography in the history of science and technology? The article explores a set of photographic collections in the UK and Canada and offers a framework for thinking about the relationship between the histories of photography, histories of science and photography, and institutional collecting practices.